2014
DOI: 10.1177/0008417414551784
|View full text |Cite
|
Sign up to set email alerts
|

Peer support as a catalyst for recovery: A mixed-methods study

Abstract: This research adds to existing literature that PSWs produce outcomes similar to nonpeer staff and struggle with boundaries related to their unique role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 34 publications
(44 reference statements)
0
35
0
2
Order By: Relevance
“…When studying the transition between hospital and community, Simpson et al (2014) found no differences between PS and standard treatment, except a hopelessness assessment -there was a lower score when PS workers were involved. Wrobleski et al (2015) again found no differences, however the sample size was so small it would be impossible to find a statistically significant difference with such high confidence intervals.…”
mentioning
confidence: 80%
“…When studying the transition between hospital and community, Simpson et al (2014) found no differences between PS and standard treatment, except a hopelessness assessment -there was a lower score when PS workers were involved. Wrobleski et al (2015) again found no differences, however the sample size was so small it would be impossible to find a statistically significant difference with such high confidence intervals.…”
mentioning
confidence: 80%
“…Wenn ich vom Anwendungsfokus der Forschungen zu Genesungsbegleitung spreche, beziehe ich mich zunächst auf ein thematisches Spektrum: Ein Großteil der Artikel und Aufsätze aus der psychiatrisch-psychologischen Literatur nimmt die therapeutische Wirksamkeit von Peer-Arbeit in den Blick -sowohl innerhalb Deutschlands als auch in anderen Ländern (Dixon, Krauss und Lehman 1994;Felton et al 1995;Davidson et al 1999;Bock et al 2013;Fisher et al 2015;Mahlke et al 2015a;Wrobleski et al 2015;Cronise et al 2016;Heumann et al 2016a;Salzer et al 2016 (Przyborski und Wohlrab-Sahr 2013). Die Autorinnen verwiesen auf die Eigenheit aller qualitativen Verfahren (sofern sie nicht nur als Ergänzung quantitativer Fragestellungen fungieren), ein per se rekonstruktives Verhältnis zu ihrem Forschungsgegenstand zu haben.…”
Section: Anwendungsorientierte Studien Und Forschungenunclassified
“…To overcome these challenges, recovery-oriented services have been integrated into the mental health care systems for decades to support persons with schizophrenia [6]. Peer-delivered intervention is one such service that emerged in the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, self-declaration and self-e cacy are emphasized in peer support services to help service users overcome internalized stigma and a sense of powerlessness [4,6,8]. Empirical evidence also shows that peer support services can be effective in installing hope and overcoming the aforementioned di culties, both of which can help persons with psychiatric disabilities to engage more actively in their journey of recovery [9,10].…”
Section: Introductionmentioning
confidence: 99%